2004
DOI: 10.1021/ma048864i
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation in Thin Films of Poly(styrene-block-4-vinylpyridine) Copolymer−2-(4‘-Hydroxybenzeneazo)benzoic Acid Assembly

Abstract: The fine structure of thin films of poly(styrene-block-4-vinylpyridine) copolymer−2-(4‘-hydroxybenzeneazo)benzoic acid (PS-PVP+HABA) assembly has been studied using the combination of atomic force microscopy, ellipsometry, X-ray reflectivity, GISAXS, XPS, and XPEEM. The films consist of cylindrical nanodomains formed by PVP+HABA associates surrounded by PS matrix. Alignment of the domains can be switched upon exposure to vapors of different solvents from the parallel to perpendicular orientation and vice versa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
181
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(197 citation statements)
references
References 42 publications
15
181
1
Order By: Relevance
“…33−35 For supramolecular thin films, the effects of annealing solvents on the morphology of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) with 2-(4′-hydroxybenzeneazo) benzoic acid (HABA) molecules have been reported by Minko and co-workers. 22,36,37 They found that as films were annealed by chloroform, the P4VP(HABA) cylindrical microdomains were parallel to the surface, while annealed by 1,4-dioxane, the cylinders were perpendicular to the surface, which was attributed to the different selectivity of the solvents to each phase. The previous discussions of block copolymer-based supramolecules have been generally under the presumption that the small molecules are firmly grafted on the polymer chains.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33−35 For supramolecular thin films, the effects of annealing solvents on the morphology of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) with 2-(4′-hydroxybenzeneazo) benzoic acid (HABA) molecules have been reported by Minko and co-workers. 22,36,37 They found that as films were annealed by chloroform, the P4VP(HABA) cylindrical microdomains were parallel to the surface, while annealed by 1,4-dioxane, the cylinders were perpendicular to the surface, which was attributed to the different selectivity of the solvents to each phase. The previous discussions of block copolymer-based supramolecules have been generally under the presumption that the small molecules are firmly grafted on the polymer chains.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lateral structures are of special interest, e.g. for their use in organized inorganic substrates [3,4] and for the preparation of nanoporous membranes [5,6]. Solvent vapor induced annealing offers a simple and flexible method to create ordered structures with a potentially high degree of controllability through careful choice of solvent [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Association of small organic molecules with one of the polymer blocks of the starting block copolymers via weak forces of attractions, like electrostatic interactions, van der Waals forces and hydrogen bonding, has become a widely adopted approach for the fine-tuning of the block copolymer morphology in solution [14], bulk [15,16] and in thin films [17][18][19][20][21][22][23][24][25][26][27]. In a further step, the interacting small molecules can be removed by dissolution in a selective solvent, and nanoporous materials can be obtained [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In a further step, the interacting small molecules can be removed by dissolution in a selective solvent, and nanoporous materials can be obtained [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation